Whole-blood incubation with the Neisseria meningitidis lpxL1 mutant induces less pro-inflammatory cytokines than the wild type, and IL-10 reduces the MyD88-dependent cytokines. Issue 2 (February 2018) - Aass, Hans Christian D; Hellum, Marit; Trøseid, Anne-Marie Siebke; Brandtzaeg, Petter; Berg, Jens Petter; Øvstebø, Reidun; Henriksson, Carola Elisabeth
Levels of bacterial LPS, pro-inflammatory cytokines and IL-10 are related to the severity of meningococcal septicaemia. Patients infected with a Neisseria meninigitidis lpxL1 mutant ( Nm -mutant) with penta-acylated lipid A present with a milder meningococcal disease than those infected with hexa-acylated Nm wild type ( Nm -wt). The aim was to compare the pro-inflammatory responses after ex vivo incubation with the heat-inactivated Nm -wt or the Nm -mutant in citrated whole blood, and the modulating effects of IL-10. Concomitantly, we measured intracellular IL-6, IL-8 and TNF-α to elucidate which cell types were responsible for the pro-inflammatory responses. Incubation with Nm -wt (10 6 /ml;10 7 /ml;10 8 /ml) resulted in a dose-dependent increase of the MyD88-dependent pro-inflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α), which were mainly derived from monocytes. In comparison, only 10 8 /ml of the Nm -mutant significantly increased the concentration of these cytokines. The MyD88-independent cytokines (IP-10, RANTES) were evidently increased after incubation with the Nm -wt but were unaffected by the Nm -mutant. Co-incubation with IL-10 significantly reduced the concentrations of the MyD88-dependent cytokines induced by both the Nm -wt and the Nm -mutant, whereas the MyD88-independent cytokines were almost unaffected. In summary, the Nm -mutant is a weaker inducer of the MyD88-dependent/independent cytokines than the Nm -wt in whole blood, and IL-10 attenuates the Nm -stimulated increase in MyD88-dependent pro-inflammatory cytokines.